A Call For Solidarity:Pro-Palestinian Activity in the Trucial States, 1936–39. Issue 1 (2nd January 2021) - Haller, Niklas A.
Abstract: While the contemporary political and economic ties between the Gulf region and the Levant are widely acknowledged, the deeper historical roots of this modern relationship are rarely recognized in light of persistent narratives of the Gulf's relative isolation before the discovery of its hydrocarbon wealth. Building on a study of the British archival record, this article contributes to a challenge of such narratives by examining one of the earliest instances in which mutual ties became manifest: the political and financial support for the Arabs of Palestine by the population of the Trucial States (the contemporary United Arab Emirates) in the interwar years. As is shown, the development of pro-Palestinian sentiment was enabled not only by an earlier expansion of education in the Trucial States, but also by rapidly developing communication links between the Gulf and the wider Arab world. As a result of these developments, the population of the Trucial States was subject to –– and proved receptive to –– calls for Arab and Muslim solidarity emanating from Palestine in the late 1930s.